Pengaruh Metode Pembelajaran Inkuiri Berbasis VAK (Visualisasi, Auditori, Kinestetik) Terhadap Hasil Belajar Mata Pelajaran Kimia Pokok Bahasan Ikatan Kimia Pada Siswa Kelas X (Sepuluh) Jurusan Teknik Kendaraan Ringan Otomotif SMK GKST I Tentena - Silva Anita Pesak (Jurusan Kimia FMIPA UNM, 2022)
This study aims to improve learning outcomes of Chemical Bonds Basic Chemistry Subjects and determine the effect of VAK-based inquiry learning methods (Visualization, Auditory, Kinesthetic) on learning outcomes of Chemical Bonds Basic Chemistry Subjects. This research was conducted at SMK GKST I Tentena, Department of Automotive Light Vehicle Engineering (TKRO), in class X (Ten), academic year 2021/2022. The hypothesis of this research is: the use of VAK-based inquiry learning methods can improve student learning outcomes. The results of this study clearly indicated that there was a positive and significant effect between the VAK-based inquiry learning method on learning outcomes for chemistry subjects.